Cutaneous metastasis: clinicopathological study of 72 patients from a tertiary care center in Lebanon. (4th April 2013) - El Khoury, Jinane; Khalifeh, Ibrahim; Kibbi, Abdul‐Ghani; Abbas, Ossama
Abstract Background Cutaneous metastasis is the result of malignant cell spread from primary malignancy to the skin. This is not uncommon, and rates reported in the literature are as high as 10.4%. To the best of our knowledge, there are no studies assessing the epidemiologic, clinical, and histopathological features of cutaneous metastasis in our region. Objective To assess the clinical and histopathological findings of all patients diagnosed with cutaneous metastasis at the American University of Beirut – Medical Center (AUB‐MC) and to compare our findings with those published in the literature. Methods Retrospective clinical and histopathologic evaluation of all cases diagnosed as cutaneous metastasis at AUB‐MC between 1992 and 2010. Results A total of 72 patients (50 females and 22 males) were identified. The mean age at diagnosis was 55.2 years. The most common primary cancer was breast cancer in women and laryngeal cancer in men. The most common clinical presentation was a single nodule in 27% of cases followed by multiple nodules in 23%. Cutaneous metastasis lesions were asymptomatic in the majority. The chest was the most commonly affected site. On microscopy, the majority of metastatic cases were adenocarcinomas (74%). Conclusion This is, to our knowledge, the first study characterizing the epidemiological, clinical, and histopathological features of cutaneous metastasis in the Lebanese population. The clinical and histopathological features observed were in concordance with the published literature, with minor differences.